Peranan Dinas Tenaga Kerja dan Sertifikasi Kompetensi (DTKSK) Dalam Penyelesaian Perselisihan Hubungan Industrial Melalui Mediasi di Kota Denpasar - Anak Agung Alit Ista Damayanti; I Nyoman Putu Budiartha; I Gusti Agung Ayu Gita Pritayanti Dinar (Fakultas Hukum Universitas Warmadewa, 2024)
The Denpasar City Manpower and Competency Certification Office (DTKSK) is a government agency that has the function of fostering, controlling and supervising in the field of labor. However, in reality there are still many cases of industrial relations disputes. This study examines two problems, namely how the role of DTKSK Denpasar City in optimizing the settlement of industrial relations disputes through mediation and what are the inhibiting factors and efforts made by DTKSK Denpasar City in resolving industrial relations disputes through mediation?